FORMATION AND DEVELOPMENT OF THE PROFESSIONAL THINKING IN FUTURE GRAPHIC DESIGNERS WITH THE USE OF TIPS/TRIZ METHODS - Lagaeva, T.; Simac, A. (Art and Design, 2023)
Purpose: the present article is highlighting the experience of the Theory of Inventive Problems Solving use for the formation and development of professional thinking in students studying graphic design at the “Ion Creanga” State Pedagogical University of Chisinau. Меthodology. The research used the methods of contradictions solving TIPS/TRIZ, as well as the semiotic, hermeneutic, systemic, structural, morphological and interdisciplinary approaches. The authors also used the the Theory of critical thinking (Ch. Temple, D. Steel, K. Meredith) and the Project method. Results. The article describes the experience and results of the implementation of the curriculum "Fundamentals of artistic literacy using TRIZ methods" for students of graphic design. The methods of teaching the basics of artistic literacy through the prism of TRIZ methods are analyzed and systematized, stimulating the development of critical and creative thinking of future graphic designers. The application of TRIZ methods had a positive impact on the process of formation and development of students’ professional artistic thinking. Scientific novelty. The scientific novelty consists in the fact that the authors used the TRIZ methods structure for the study and understanding of the modern visual language for the creation of design objects, and afterwards for the formation and development of the professional artistic thinking of the graphic design students. Practical significance. The practical significance of the research consists in the elaboration of the author course “The Fundamentals of the Artistic Literacy with the Use of TRIZ Methods” for the graphic design students from the “Ion Creanga” State Pedagogical University of Chisinau.